Analisis Efektivitas Social Media Marketing Dan Variasi Produk Terhadap Keputusan Pembelian Sepatu Lokal PVN (Studi Kasus Pada Pengguna PVN Di Karawang) - Nuraini, Neni; Sudrajat, Ajat (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to analyze the effectiveness of Social Media Marketing and Product Variety on Purchasing Decisions for PVN local shoes. The method used is a quantitative approach with the population being people who live in Karawang Regency and actively use or know the PVN Shoes brand, the sample taken is 100 people. The type of data is primary data taken directly from respondents' answers through a questionnaire with a Likert scale. Data validity testing is carried out through the Stuctural Equation Modeling (SEM) method using Partial Least Square (PLS) or SEM - PLS. The model equations analyzed are the Measurement Model (Outer Model) and the Structural Model (Inner Model). The test results state that the Social Media Marketing and Product Variety variables effectively influence Purchasing Decisions.